2011
DOI: 10.1245/s10434-011-1912-z
|View full text |Cite
|
Sign up to set email alerts
|

MRI Staging After Neoadjuvant Chemotherapy for Breast Cancer: Does Tumor Biology Affect Accuracy?

Abstract: MRI is an effective tool for predicting response to NAC. The accuracy of MRI in estimating postchemotherapy tumor size varies with tumor subtype. It is highest in ER-/HER2+ and TN and lowest in luminal tumors. Knowledge of how tumor subtype affects MRI accuracy can guide recommendations for surgery following NAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
67
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(77 citation statements)
references
References 21 publications
7
67
0
3
Order By: Relevance
“…Interestingly, no pCRs were observed among the 60 patients evaluable for this analysis, making this endpoint impossible to study. Our institutional average pCR in the ER/PR+ population is 7%, reflecting national data [13]. There were also no instances of disease progression during NCT.…”
Section: Discussionsupporting
confidence: 64%
“…Interestingly, no pCRs were observed among the 60 patients evaluable for this analysis, making this endpoint impossible to study. Our institutional average pCR in the ER/PR+ population is 7%, reflecting national data [13]. There were also no instances of disease progression during NCT.…”
Section: Discussionsupporting
confidence: 64%
“…In addition, among HER2-negative tumors, the accuracy of MRI for predicting pCR was increased in hormone receptor-negative cancers compared with hormone receptor positive-cancers and was also improved in high-proliferation tumors compared with low-proliferation tumors (13). In another study, MRI more accurately predicted tumor sizes following NAC in HER2-positive and triple-nega- Residual DCIS (%) tive tumors compared with luminal tumors (14). By contrast, De Los Santos et al (15) reported that the molecular subtype was not identified to significantly affect the sensitivity, specificity, PPV or NPV of MRI for the prediction of pathological responses.…”
Section: Discussionmentioning
confidence: 95%
“…DCE-MRI precisely defines the disease extent through selected morphokinetic parameters and is considered a good pCR discriminator regardless of the tumor subtype. DCE-MRI provides good correlation, even in cases of lobular carcinoma, multifocal and multicentric disease, allowing for early dynamic and metabolic assessment of tumors: tumor morphology changes, regression and enhancement patterns, and tridimensional and volume evaluation, which all define a specific "MRI phenotype" (19)(20)(21)(22). The morphokinetic features in DCE-MRI examinations are based on recommended oncologic imaging measurement tools (19)(20)(21)(22).…”
Section: Resultsmentioning
confidence: 99%